2018
DOI: 10.1021/acs.iecr.8b00985
|View full text |Cite
|
Sign up to set email alerts
|

The Coming Age of Insect Cells for Manufacturing and Development of Protein Therapeutics

Abstract: Protein therapeutics is a rapidly growing segment of the pharmaceutical market. Currently, the majority of protein therapeutics are manufactured in mammalian cells for their ability to generate safe and efficacious human-like glycoproteins. The high cost of using mammalian cells for manufacturing has motivated a constant search for alternative host platforms. Insect cells have begun to emerge as a promising candidate, largely due to the development of the baculovirus expression vector system. While there are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 121 publications
0
45
0
Order By: Relevance
“…The MAPS strategy introduced here addresses such a need by providing a simple method for identifying immunologically relevant, promiscuous MHCII‐binding peptides. Incorporation of the MAPS strategy into the vaccine development process could accelerate T cell epitope identification and expedite the development and manufacturing of novel vaccines . Beyond vaccine development, our observations indicate that MAPS and similar screening strategies should provide valuable insights relevant to broadly applicable peptide‐based therapies, vaccines, and diagnostic tools necessary to protect ethnically diverse populations.…”
Section: Discussionmentioning
confidence: 97%
“…The MAPS strategy introduced here addresses such a need by providing a simple method for identifying immunologically relevant, promiscuous MHCII‐binding peptides. Incorporation of the MAPS strategy into the vaccine development process could accelerate T cell epitope identification and expedite the development and manufacturing of novel vaccines . Beyond vaccine development, our observations indicate that MAPS and similar screening strategies should provide valuable insights relevant to broadly applicable peptide‐based therapies, vaccines, and diagnostic tools necessary to protect ethnically diverse populations.…”
Section: Discussionmentioning
confidence: 97%
“…Insect cells are not able to carry out Nglycosylation, but this issue can be solved by introducing mammalian glycosyltransferases into insect cells or by the coexpression of these enzymes together with the gene of interest in baculoviruses (Le et al, 2018). The most common cell line used for the baculovirus expression system is Sf9 (Van Oers et al, 2018;Yee et al, 2018;Ghasemi et al, 2019). In addition to Sf9 cells, S2, Sf21, Tn-368, and High-Five TM cells are also used for the expression of recombinant proteins (Contreras-Gómez et al, 2014;Felberbaum, 2015).…”
Section: Insect Cellsmentioning
confidence: 99%
“…CRISPR is expected to instigate a rapid expansion of engineering approaches to achieve enhanced expression of multiple genes in insect cells. These current and expected future developments in engineering insect cells for enhanced expression of humanized proteins are dissolving perceived disadvantages to bring about the upcoming age of the use of insect cells for the development and manufacturing of therapeutic proteins (Yee et al, 2018). Pazmiño-Ibarra et al (2019) reported the use of a CRISPR/Cas9 system for the engineering of baculovirus to improve its performance as a protein expression vector.…”
Section: Insect Cellsmentioning
confidence: 99%
“… 138 , 193 (b) Insect cell and insect cell-based baculovirus glycosylation systems have been remodeled to obtain full-length bianntenary N-linked glycans without α1,3 fucose residues. 194 (c) Remodeled plant glycosylation systems have reduced arabinosylation of prolines and produced human O -GalNAc glycans and full-length bianntenary N -linked glycans. 195 (d) Extensive remodeling of yeast glycosylation pathways have worked to eliminate oligo-mannose structures from N - and O -linked glycans and introduce human terminally sialylated, full-length human O -linked and N -linked glycans.…”
Section: Synthetic Glycosylation Systemsmentioning
confidence: 99%